Real-World Impact of Physician and Patient Discordance on Health-Related Quality of Life in US Patients with Acute Myeloid Leukemia - L. Elise Horvath Walsh; Alex Rider; James Piercy; James Pike; Samuel Wilson; Bhavik J. Pandya; Bruno C. Medeiros (Oncology and Therapy, 2019)
Abstract Introduction There is limited understanding concerning the health-related quality of life (HRQoL) in acute myeloid leukemia (AML) patients. Due to an overlap of symptoms, it can be difficult to separate disease versus treatment-related effects. Study objectives were to understand the impact of factors that might influence patients’ HRQoL, assess the degree of concordance in symptom reporting by patients and physicians, and assess the impact of any discordance on HRQoL in AML patients. Methods Physicians in the USA captured demographics, current AML treatment and symptoms for 82 AML patients who completed the Functional Assessment of Cancer Therapy-Leukemia (FACT-Leu), 5-Dimension EuroQol Questionnaire (EQ-5D-3L) and Cancer Treatment Satisfaction Questionnaire (CTSQ). Effect size (ES) and clinically meaningful differences between AML subgroups were assessed, as was the impact of disagreement between patients and physicians regarding symptom recognition. Results Clinically meaningful lower overall FACT-Leu scores were observed for: relapsed/refractory versus non-relapsed/refractory AML patients (92.5 vs. 103.7; P = 0.09; ES = 0.439), hypomethylating agent (HMA) monotherapy versus other therapies in patients with low treatment intensity (89.9 vs. 112.9; P = 0.0021; ES = 0.971) and presence/absence of FLT3-ITD mutation (85.5 vs. 100; P = 0.148; ES = 0.816). Differences in health state were also clinically meaningful between patients with/without FLT3-ITD; EQ-5D-Visual Analog Scale (VAS) (47.6 vs. 63.7; P = 0.0428; ES = 0.816). Patients were more likely than physicians to report bruising (κ = 0.1292), fatigue (κ = 0.0836), bleeding (κ = 0.0177), weight loss (κ = 0.0821) and appetite loss (κ = − 0.0246). FACT-Leu was associated with patient-physician discordance on bleeding (difference − 14.12; P = 0.046), weight loss (− 21.22; P = 0.001) and appetite loss (− 12.58; P = 0.027). Conclusions HRQoL is generally low for AML patients, especially for particular subgroups. Discordance in symptom reporting between patients and physicians was common and associated with further negative impacts on HRQoL. There may be many reasons for this but better communication between physicians and patients may lead to shared objectives and improvement in patients’ HRQoL. Funding Astellas Pharma, Inc.